Changing trends in the management of corpus luteum haemorrhage - Gupta, Avantika; Nayak, Deepthi; Tiwari, Purnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Corpus luteal haemorrhage usually causes only mild symptoms and resolve spontaneously, however, it can cause massive bleeding in certain patients with coagulation or bleeding disorders. Over a decade, the management of corpus luteum haemorrhage has shifted from surgical to conservative management. This article focuses on selection of patients for conservative management so that the morbidities associated with the surgery can be avoided. Conservative management includes optimization of oxygen carrying capacity of blood, correction of coagulopathy and appropriate analgesia. It can be recurrent in certain high-risk group of patients who will need long term suppression of ovulation.